Age-Related Differences in Response to High-Fat Feeding on Adipose Tissue and Metabolic Profile in ZDSD Rats. (20th May 2013) - Davis, Jeremy E.; Cain, James; Banz, William J.; Peterson, Richard G.
Abstract : The recruitment of new fat cells through adipogenesis may prevent the development of obesity-related comorbidities. However, adipogenic capacity is markedly reduced in mature adults. This study examined how initiation of high-fat feeding at different phases of adulthood modified adipose tissue (AT) morphology and obesity phenotype in obese and diabetic Zucker Diabetic Sprague Dawley (ZDSD) rats. For this, rodents were provided high-fat diet (HFD) beginning at 63, 84, or 112 d after parturition until termination ( n = 6 ) . At termination, ZDSD rats fed HFD beginning at 63 d after parturition (early adulthood) exhibited greater body fat and lower lean mass without significant changes to energy intake or body weight. Moreover, early high fat feeding increased adipocyte size and number, whereas these effects were absent at 84 or 112 d after parturition. At 126 d after parturition, there were no detectable transcript differences in PPAR γ or C/EBP α . However, rodents provided HFD in early adolescence exhibited lower expression of canonical Wnt signaling intermediates. Corresponding with these changes was a marked reduction in AT-specific inflammation, as well as overall improvement in systemic glucose, lipid, and inflammatory homeostasis. Taken together, these data indicate that dietary regulation of adipocyte recruitment in adolescence may represent a major determinant of obesity phenotype.